Koncepcja dzieła sztuki Karola Irzykowskiego - aspekt estetyczny i poznawczy - Gołębiewska, Maria (Przestrzenie Teorii, 2007)
The text presents the main aesthetic theses of Karol Irzykowski, concerning the work of art. Karol Irzykowski (1873-1944) - the Polish writer, critic and theorist of literature, art and culture - considered the work of art as the specific object of culture, as the source of human aesthetic experience and, at the same time, of cognition. He admitted the art, first of all, as the result of intellectual action. That is why, the primary thesis of his aesthetics underlines the connection between the aesthetic and epistemological qualities in the work of art. The text characterises this connection and refers to the philosophical tradition, important for the ideas of Karol Irzykowski.